Agricultural Management Drive Bacterial Community Assembly in Different Compartments of Soybean Soil-Plant Continuum - Chen, Shi; Wang, Lulu; Gao, Jiamin; Zhao, Yiwen; Wang, Yang; Qi, Jiejun; Peng, Ziheng; Chen, Beibei; Pan, Haibo; Wang, Zhifeng; Gao, Hang; Jiao, Shuo; et al. (Frontiers in Microbiology, 2022)
Flowering stage of soybean is an important agronomic trait, which is important for soybean yield, quality and adaptability, and is the external expression of integrating external environmental factors and endogenous signals of the plant itself. Cropping system can change soil properties and fertility, which in turn determine plant growth and yield. The microbial community is the key regulator of plant health and production performance. Currently, there is limited understanding of the effects of cropping systems on microbial community composition, ecological processes controlling community assembly in different soil-plant continuum compartments of soybean. Here, we hope to clarify the structure and assembly process of different soybean compartments bacterial community at flowering stage through our work. The results showed that intercropping decreased the species diversity of rhizosphere and phyllosphere, and phylloaphere microbes mainly came from rhizosphere. FAPROTAX function prediction showed that indicator species sensitive to intercropping and crop rotation were involved in nitrogen/phosphorus cycle and degradation process, respectively. In addition, compared to the continuous cropping, intercropping increased the stochastic assembly processes of bacterial communities in plant-associated compartments, while crop rotation increased the complexity and stability of the rhizosphere network and the deterministic assembly process. Our study highlights the importance of intercropping and crop rotation, as well as rhizosphere and phyllosphere compartments for future crop management and sustainable agricultural regulation of crop microbial communities.